Homologous and Heterologous Phosphorylations of Human Histamine H1 Receptor in Intact Cells - Katsuhiro Miyoshi; Nozomi Kawakami; Shuhei Horio; Hiroyuki Fukui (Elsevier, 2004)
Homologous and heterologous phosphorylations of histamine H1 receptor (H1R) in intact cells were investigated using Chinese hamster ovary cells stably co-expressing c-myctagged human histamine H1 and muscarinic M3 receptors. Increase in histamine-induced homologous phosphorylation of H1R was induced in a dose- and time-dependent manner. Maximum phosphorylation of H1R by 8-fold over the basal level was induced 1 min after the stimulation, and the increased phosphorylation level was maintained over 40 min. M3 receptor-mediated heterologous phosphorylation of H1R reached maximum by 2-fold over the basal level at 5 min after the stimulation and then rapidly returned to the basal level by 40 min after the stimulation. Histamine-induced phosphorylation of H1R was partially inhibited by three protein kinase inhibitors including Ro-31-8220 for protein kinase C (PKC), KN-93 for calcium/calmodulin-dependent kinase II (CaMKII), and KT5823 for protein kinase G (PKG), while, M3-receptor-mediated phosphorylation of H1R was completely inhibited by Ro 31-8220. Protein kinase activators including phorbol 12-myristate 13-acetate (PMA), 8-bromo-cyclic GMP (8-Br-cGMP), and 8-bromo-cyclic AMP (8-Br-cAMP) induced increases in H1R phosphorylation. Increased phosphorylation of H1R, by 5-fold over the basal level, induced with a combination of PMA, 8-Br-cGMP, and 8-Br-cAMP was still lower than that with histamine. It was suggested that H1R-mediated H1R phosphorylation involves the activation of PKC, CaMKII, PKG, and other unidentified kinases including G-protein coupled receptor kinases (GRKs) and that PKC is solely involved in M3 receptor-mediated H1R phosphorylation. Keywords:: histamine H1 receptor, phosphorylation, M3 muscarinic receptor, protein kinase C, G-protein-coupled receptor kinase